Anmeldelse af Patrycja Szarek-Mason: The European Union’s Fight Against Corruption. The Evolving Policy Towards Member States and Candidate Countries - Langsted, Lars Bo (Nordisk Tidsskrift for Kriminalvidenskab, 2014)
Review of Patrycja Szarek-Mason: The European Union’s Fight Against Corruption. The Evolving Policy Towards Member States and Candidate Countries